The Caenorhabditis elegans muscle-affecting gene unc-87 encodes a novel thin filament-associated protein (The Rockefeller University Press, 1994)
Mutations in the unc-87 gene of Caenorhabditis elegans affect the structure and function of bodywall muscle, resulting in variable paralysis. We cloned the unc-87 gene by taking advantage of a transposon-induced allele of unc-87 and the correspondence of the genetic and physical maps in C. elegans. A genomic clone was isolated that alleviates the mutant phenotype when introduced into unc-87 mutants. Sequence analysis of a corresponding cDNA clone predicts a 357- amino acid, 40-kD protein that is similar to portions of the vertebrate smooth muscle proteins calponin and SM22 alpha, the Drosophila muscle protein mp20, the deduced product of the C. elegans cDNA cm7g3, and the rat neuronal protein np25. Analysis of the genomic sequence and of various transcripts represented in a cDNA library suggest that unc-87 mRNAs are subject to alternative splicing. Immunohistochemistry of wildtype and mutant animals with antibodies to an unc-87 fusion protein indicates that the gene product is localized to the I-band of bodywall muscle. Studies of the UNC-87 protein in other muscle mutants suggest that the unc-87 gene product associates with thin filaments, in a manner that does not depend on the presence of the thin filament protein tropomyosin.